Pengaruh Aromaterapi Kamboja Terhadap Kualitas Tidur Ibu Hamil Trimester Ketiga Di Wilayah Kerja Puskesmas Kedungrejo - Eka Karina Sari Priastuti; Rani Safitri (Journal of Innovative and Creativity, 2025)
Sleep disturbances are common among third-trimester pregnant women due to physical discomfort, hormonal changes, and anxiety. This study investigates the effect of frangipani aromatherapy on sleep quality in this population within the Kedungrejo Health Center area, Banyuwangi, Indonesia. A quasi-experimental design was employed with 60 participants divided into intervention and control groups. The intervention group received frangipani aromatherapy inhalation for 15 minutes before bedtime over four weeks, while the control group received standard care. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). Results showed a significant improvement in sleep quality scores in the intervention group (pre: 8.2 ± 1.5; post: 4.3 ± 1.2) compared to the control (pre: 8.1 ± 1.4; post: 7.5 ± 1.3), with p < 0.001. Data from Kedungrejo Health Center (2022-2024) indicate 527, 523, and estimated 530 pregnant women annually, with antenatal care coverage at 90.9%, 86.6%, and similar rates, highlighting the need for non-pharmacological interventions. Frangipani aromatherapy proves effective and safe for enhancing maternal sleep.